Discourse of Plastic Waste Awareness (Discourse Analysis on Instagram Account @zerowaste.id_official) - Satiya, Firli Daffa; Iswahyuhningtyas, Cici Eka (Faculty of Communication Science | Universitas Pancasila Jakarta, Indonesia, 2023)
The mainstream media is no longer able to stand independently and cannot produce news content that is fair and transparent to the public. Nowadays, the media prioritizes content that can generate profits for themselves. One issue that is considered less profitable is the environmental issue, as some media outlets believe that it is not a popular topic for public discussion. According to data published by the Ministry of Environment and Forestry in February 2019, Indonesia generates at least 64 million tons of waste, including plastic waste. In contrast, the social media platform Instagram, which is considered effective in disseminating information, is being utilized by the environmental community, such as Zero Waste Indonesia, to promote awareness about plastic waste and implement the 5R principles (Reduce, Reuse, Recycle, Rot, Refuse) through the 30 Days Zero Waste Challenge. This research adopts a critical qualitative approach, employing Norman Fairclough's Critical Discourse Analysis and examining it from an environmental communication perspective. The findings of this research suggest that Zero Waste Indonesia collaborates with various institutions and brands that share the same objectives to produce their texts. The theme of the 30 Days Zero Waste Challenge, initiated in 2018, is built upon the prevailing social issue in Indonesia, which is the plastic waste emergency. Moreover, the Zero Waste Indonesia community has successfully implemented the 5R principles in society. Academically, it is recommended to further explore environmental issues on social media using the tools of discourse analysis to provide new sources of reading material. In practical terms, it is suggested that Zero Waste Indonesia expands its presence on other social media platforms and utilizes live streaming features to convey verbal messages about plastic waste awareness, making it easier for the general public to understand.